Chemical reprogramming and transdifferentiation. (October 2017) - Xie, Xin; Fu, Yanbin; Liu, Jian
Highlights: Somatic cell reprogramming/transdifferentiation provide a new path for cell replacement therapies and drug screening. The original method for reprogramming involves the delivery of exogenous transcription factors, leading to the safety concerns about the possible genome integration. Compared to other methods, small-molecule compounds have several unique advantages, such as structural versatility and being easy to control in a time-dependent and concentration-dependent way. Here, we review the recent achievements of chemical reprogramming/transdifferentiation and discuss the advantages and challenges facing this strategy in future applications. Abstract : The revolutionizing somatic cell reprogramming/transdifferentiation technologies provide a new path for cell replacement therapies and drug screening. The original method for reprogramming involves the delivery of exogenous transcription factors, leading to the safety concerns about the possible genome integration. Many efforts have been taken to avoid genetic alteration in somatic cell reprogramming/transdifferentiation by using non-integrating gene delivery approaches, cell membrane permeable proteins, and small molecule compounds. Compared to other methods, small-molecule compounds have several unique advantages, such as structural versatility and being easy to control in a time-dependent and concentration-dependent way. More importantly, small molecules have been used as drugs to treat human diseases for thousands of years. So the small molecule approach to reprogramming might be more acceptable in clinical-related uses. In the past few years, small molecule approaches have made significant progresses in inducing pluripotent or functional differentiated cells from somatic cells. Here we review the recent achievements of chemical reprogramming/transdifferentiation and discuss the advantages and challenges facing this strategy in future applications.